PENINGKATAN PENGETAHUAN HIPERTENSI DAN PELATIHAN PENGHITUNGAN NADI DAN PENGUKURAN TEKANAN DARAH PADA KADER POSYANDU DI DESA SIDOREJO - W. Wahyuni; endah sri wahyuni; ika silvitasari (WARTA LPM, 2019)
Posyandu seniors are the center of community activities in the efforts of health services in the elderly. Posyandu as a place of activities that nuances community empowerment, The main problems faced by posyandu include facilities that are not yet adequate, lack of active cadres, lack of knowledge of cadres about health, not yet able to use appropriate technology, namely blood pressure checks, vital signs which include pulse counting , body temperature measurement and blood sugar examination, examination of gout, The aim of the activity is to help posyandu health cadres by disseminating information about hypertension knowledge and training on the use of appropriate technology by checking blood pressure, blood sugar testing, gout testing, cholesterol testing, marking measurements vital signs through training. Method; the methods implemented in this activity are training, mentoring after training activities and competitions to find out the improvement of both knowledge and skill results; Cadre's knowledge of hypertension increases, cadre skills in terms of blood pressure measurement and measurement of vital signs are increasingly skilled. The resulting output of hypertension care pocket books with ISBNs, intellectual property rights, scientific articles published in community service journals with ISSN, posters for elderly, feedback sheets, publications in online media, publications in print media the conclusions of cadre knowledge about hypertension are increasing. Skill of measuringbloodpressureincreases